Research Trends in Collaborative Governance: A Bibliometric Analysis - Anton Hilman; Asep Sumaryana; Ramadhan Pancasilawan (Department of Public Administration, 2023)
Collaborative Governance terms become a phenomenon in the private sector and the public sector. Collaborative Governance is conceptualized as public governance in decision-making processes and actions that involve actors from government and other sectors. Collaborative development Governance plays an important role in solving public problems, especially on economic and environmental issues. The method used in seeing the development of the concept Collaborative Governance is carried out using the bibliometric analysis method. This research provides knowledge and makes recommendations for journal readers and writers who can become references by adjusting the issues chosen. This research highlights the trend of research collaborative Governance is seen from the authors and journals that have written the most regarding collaborative concepts governance. The results of this study indicate the writing of articles about the concept collaborative Governance fluctuates every year. The biggest contributor to concept thinking collaborative governance seen from the highest number of citations namely Kirk Emerson a researcher from the University of Arizona. Collaborative governance as a concept from 2020 to 2023 has trending contextual issues related to Covid-19, air pollution, cities, environmental governance and urban development. The productivity of international journals is related to the concept collaborative governance namely the Journal of Public Research Administration.